Peningkatan Service Quality of Employee dengan Servant Leadership dan Self-Efficacy di Kementerian Kelautan dan Perikanan (KKP) - Syavina Amalia Putri; Tri Siwi Agustina; Peggy Delita Merida; Anis Eliyana (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2021)
The concept of servant leadership has been referred to as a form of leadership approach that is committed to empowering the abilities and needs of employees. Currently, the concept of leadership has attracted the attention of most researchers in terms of the increasing number of moral violations of management and workplace irregularities. This study aims to know how the direct influence of servant leadership and self-efficacy on employee service quality and the effect of servant leadership moderation on two variables, namely self-efficacy of service quality of employees and service quality of employees. The researcher used Structural Equation Modeling (SEM) methodologically with AMOSGrapchics. There were two studies in this research. The data in the first and second studies was obtained from the distribution of online questionnaires to the State Civil Service (SCS) of the Ministry of Marine Affairs and Fisheries (KKP). A total of 222 Civil Servants were available. The study resulted in several tests related to (1) servant leadership has a significant effect on the service quality of Civil Servants employees at KKP, (2) self-efficacy has a significant effect on employee service quality, and (3) servant leadership can significantly moderate between self-efficacy and service quality employees of Civil Servants at the KKP.